2015
DOI: 10.1007/s12221-015-1035-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of surface functionalized graphene oxide nanosheet and its multicomponent dye removal ability from wastewater

Abstract: Amine functionalized graphene oxide (AF-GO) nanosheet was prepared and used to remove anionic dyes from multicomponent (binary) systems. The AF-GO was characterized by FTIR and SEM. Acid Blue 92 (AB92), Acid Red 14 (AR14), and Direct Green 6 (DG6) were used as anionic dyes. The dye adsorption kinetics and isotherm followed the pseudosecond order and Langmuir model, respectively. Adsorption capacity of AF-GO for AB92, AR14 and DG6 was 60, 64 and 65 mg/g, respectively. The results showed that AF-GO nanosheet was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…3. It can be clearly observed that the surface of rGO comprises crumpled and corrugated sheets which are both intrinsic properties of graphenic sheets [32][33][34]. From Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…3. It can be clearly observed that the surface of rGO comprises crumpled and corrugated sheets which are both intrinsic properties of graphenic sheets [32][33][34]. From Fig.…”
Section: Resultsmentioning
confidence: 85%
“…In our research, we used a top-down approach for synthesis of reduced graphene oxide (rGO) from graphite. Graphite flake powder was first thoroughly oxidized by means of chemical agents including H 2 SO 4 , KMnO 4 , and H 2 O 2 using the modified Hummers' method [32]. In the next step, the rGO was prepared using a simple and green hydrothermal method in an alkaline medium [33].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the stronger binding sites are occupied first, and that the binding strength decreases with increasing site occupancy. 69 The Freundlich isotherm is expressed as:where K f (mg g −1 ) is the adsorption capacity at unit concentration and 1/ n is the adsorption intensity. The 1/ n values indicate the type of isotherm: irreversible (1/ n = 0), favorable (0 < 1/ n < 1) and unfavorable (1/ n > 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that the stronger binding sites are occupied first, and that the binding strength decreases with increasing site occupancy. 69 The Freundlich isotherm is expressed as:…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Subsequently, the high significant electrostatic attraction occurs between the positively charged surface of the adsorbent (NH 3 + ) and negatively charged anionic dye molecules [56]. As the pH of the system increases, the number of positively charged sites decreases.…”
Section: 4 3d Surface Plot Analysis and Optimization Processmentioning
confidence: 99%